7x+6=9x+x

Simple and best practice solution for 7x+6=9x+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+6=9x+x equation:


Simplifying
7x + 6 = 9x + x

Reorder the terms:
6 + 7x = 9x + x

Combine like terms: 9x + x = 10x
6 + 7x = 10x

Solving
6 + 7x = 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
6 + 7x + -10x = 10x + -10x

Combine like terms: 7x + -10x = -3x
6 + -3x = 10x + -10x

Combine like terms: 10x + -10x = 0
6 + -3x = 0

Add '-6' to each side of the equation.
6 + -6 + -3x = 0 + -6

Combine like terms: 6 + -6 = 0
0 + -3x = 0 + -6
-3x = 0 + -6

Combine like terms: 0 + -6 = -6
-3x = -6

Divide each side by '-3'.
x = 2

Simplifying
x = 2

See similar equations:

| 250+.10y=350 | | x^2+y^2+30x-2y+210=0 | | 8.5X=11 | | x+.10y=350 | | 600+600= | | 5(x+5)=-5(2x-3)+x | | 23+6y-15=62 | | 5y=x+19 | | 189s=99+10 | | 7x-18=9x+4 | | 5(y-2)=-5y+40 | | 10x=4y+16 | | -c^2-5c+66= | | 3u+37=-5(u+9) | | 10x+x-4x= | | 5x-3-x=14-3x+11 | | 2k+8-4k=28 | | -18x^2+6x+24=0 | | Z^6=1 | | 23+14s=65 | | 23s+14=65 | | 3y^2-2x^2+2xy-6=0 | | 14x+3x+7x= | | 3.2=1.35h | | 2(j-20)+3=10 | | 3*1+y=9 | | 3*4+y=9 | | y-9=-11-y | | 4p-24=27-13p | | m-56=101 | | 3y+7=2y+7 | | 2y-5x=-60 |

Equations solver categories